DESCRIPTION OF ILLNESS PERCEPTION IN DIABETIC RETINOPATHY PATIENTS AT RSD DR. SOEBANDI JEMBER: GAMBARAN PERSEPSI PENYAKIT PADA PASIEN RETINOPATI DIABETIK DI RSD DR. SOEBANDI JEMBER - Az-Zuhri, Miratul 'Uzaimah; Siswoyo, Siswoyo; Widayati, Nur (Ikatan Lembaga Mahasiswa Ilmu Keperawatan Indonesia, 2022)
Introduction: Diabetic retinopathy patients have different perceptions about how to take care of themselves. Some have a negative perception of dealing with their illness, which can cause the patient to become depressed, it affects the patient in controlling blood sugar levels, so increasing risk of developing diabetic retinopathy. The negative illness perception causes the patient's lack of awareness to check his eye condition regularly so that it can affect the patient's health condition. This study aimed to analyze the illness perception in patients with diabetic retinopathy at RSD dr. Soebandi Jember. Method: This research was quantitative research using a descriptive design. Respondents in this study were 34 diabetic retinopathy patients obtained by the total sampling technique. Data were collected using the Brief Illness Perception Questionnaire (B-IPQ) and analyzed using univariate data analysis. Result: The results showed an average value of illness perception was 51.44 (SD = 16.85), indicating that diabetic retinopathy was still considered a threat by the respondents. The indicator with the highest value is concern, while the indicator with the lowest value is treatment control. In this study, patients perceive their disease as a threat due to a lack of knowledge about diabetic retinopathy, symptoms of the disease, and patient concerns about their disease. Conclusion: The patient's illness perception needs to be formed to overcome the disease because it can impact the patient's health. One factor influencing illness perception is knowledge because patients with good knowledge can implement the information they have to maintain their health. Providing health education about diabetic retinopathy is needed to improve the patient's perception of the disease.